(3eTcGI GdeUGHjMs - (3eMeO Hf YHO Gddg GdNWjH GdYeQj, CHh YHO Gddg, hdj GdOjf, GdJHQjRj , (B741 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg fMeOg hfSJYjfg hfSJZaQg hfYhP HGddg ef CfaSfG hef SjFGJ CYeGdfG hSejJ GdcJGH HeTcGI GdeUGHjMs
(3BNQgG (B:s
(3Yf HgR Hf Mcje Yf CHjg Yf LOg Cfg SeY QShd Gddg Udi Gddg Ydjg hSde jbhd aj bhdg JYGdi (B{ (3cfJe NjQ CeI GNQLJ ddfGS (B} (3bGd (B: " (3CfJe JJehf SHYjf CeI CfJe NjQgG hCcQegG Ydi Gddg JYGdi (B" (3QhGg GdJQePj hGHf eGLg hGdOGQej s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 234s
(3eYLe GdeDdajf (B3 / 437s
(3cTa GdXfhf (B2 / 1699s
(3eYLe GdeWHhYGJ (B627s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs